Effect of ultra-high pressure on the relationship between endogenous proteases and protein degradation of Yesso scallop (Mizuhopecten yessoensis) adductor muscle during iced storage - Xinyao Zeng; Dexin Jiao; Xiaona Yu; Lihang Chen; Ying Sun; Aoran Guo; Chen Zhu; Jinshan Wu; Jingsheng Liu; Huimin Liu (Food Chemistry: X, 2022)
This study aimed to explore the effect of ultra-high pressure (UHP) treatment (100–500 MPa, 5 min, 15 ± 1 ℃) on the relationship between endogenous proteases and protein degradation of Yesso scallop (Mizuhopecten yessoensis) adductor muscle during iced storage for 28 days. Our findings showed that the UHP treatment kept the water holding capacity stable, increased the hardness and decreased the springiness of scallop adductor muscle during iced storage. 400 and 500 MPa UHP treatments caused protein denaturation and oxidation significantly, decreased protein degradation rate and inhibited the activities of endogenous proteases. According to the correlation analysis, the activities of cathepsin B, D, H, L, calpain and serine protease were positively correlated with TCA-soluble peptides. The activities of endogenous proteases were significantly correlated with protein degradation. Therefore, the effect of UHP on endogenous protease caused the protein degradation rate to slow down and prevented the texture deterioration in scallops.